Coordinated slag Disposal From Horizontal Boreholes During Hydraulic Cutting Based on Two-Phase Flow Theory - Zhang, Yongjiang; Ji, Fei; Zou, Quanle (Frontiers in Earth Science, 2022)
The purpose of the study is to explore the mechanism of coordinated slag disposal in the hydraulic cutting process, ensure the safety implementation of the hydraulic cutting operation and increase the success rate of hydraulic cutting. In the ultra-high pressure hydraulic cutting technique, the method for determining the cutting pressure is ambiguous, the coordination mechanism of various factors (including cutting pressure and coal-dropping speed) lingers unclarified; the slag disposal mechanism during hydraulic cutting is inexplicit. Aiming at these problems, a model for coordinated slag disposal during hydraulic cutting based on coal–water two-phase flow was established. The critical flow velocity in the moving laminar flow regime is taken as that during the coordinated slag disposal from boreholes. The relationship curve between the coal-dropping speed and cutting pressure under different Protodyakonov coefficients of coal seams was obtained. Hence, the model for coordinated slag disposal during hydraulic cutting was established; the selection interval of reasonable pressure for coordinated slag disposal during hydraulic cutting was determined. The reasonable cutting pressure for slag disposal in coal seams with a Protodyakonov coefficient of 0.48 was determined as about 80MPa. During the cutting test, the average net gas extraction from the boreholes for hydraulic cutting was 4.5 times larger than that from the conventional boreholes. Furthermore, the gas permeability coefficient of the boreholes for hydraulic cutting increased by 25 times; the effective extraction radius was more than doubled. It indicated that the model for reasonably selecting the cutting pressure based on the coordinated slag disposal theory can effectively guide the selection of the cutting pressure on site. While solving various problems occurring in the hydraulic cutting process on site, the model can be used to improve the cutting effect, which provides a theoretical basis for reasonably selecting the pressure during ultra-high pressure hydraulic cutting.